Cadenas productivas: una alternativa para afrontar la integración regional - Pierce Diez Canseco, Leslie (2003)
The dynamism of the trade integration process within Latin America opens up opportunities and risks for Peru. The great opportunity to access larger and more developed markets than ours also means the risk of greater competitive pressure in the domestic market, since products from other countries will enter Peru with the same advantages. In this context, production chains emerge as an alternative for collective efficiency, but their development requires certain conditions: elimination of cost overruns, coherent macroeconomic policies, identification of competitive advantages, and an environment that generates stability and trust.